Non-Ideal Kinetics for Radical Polymerization of N-Vinylpyrrolidone - Vasishtha, Rita; Srivastava, A.K. (Asian Journal of Chemistry, 2010)
The radical polymerisation of N-vinylpyrrolidone (N-VP), initiated by α-α´ azobisisobutyronitrile (AIBN) in the presence of imidazolium-p-chloro-phenacylide (ICPY) in dimethylformamide at 60ºC follows non-ideal kinetics. The kinetic equation for the present system is Rpα [AIBN]1.50 [ICPY]1.50 [N-VP]2.0. The degradative chain transfer and primary radical termination reasonably explains the kinetic non-ideality.